Abdul Kalam's futuristic India - Gandhi, P. Jegadish (New Delhi, 2006)
The vibrant visionary thoughts with viable mission modes of President A.P.J. Abdul Kalam have now become a phenomenon in Indian public life. His autobiography wings of fire has impacted almost every Indian thought. His interactions with young people have ignited their minds to unlease their latent potent power so as to widen their positive nation building activities. Dr. Kalam envisions an empowered and developed India by 2020 through competitive and innovative technology driven societal transformation. He also charted various state government development mission mode models based on their core competencies. Dr. Kalam has a simplicity and humility which instantly endears him to all who come into contact with him. His social dialogues break conventional barriers and build bridges of new human relations in a pluralistic society. It is unheard in the history of post independent India that a President of India is so committed to spearhead a social revolution as Dr. Kalam. Dr. Kalam's vision has a number of ideas which are similar to those of the new Institutional School Neo classical School with their emphasis on the primacy of markets and the concept of embodied technology and its role in development and the importance of innovations and entrepreneurs in development as stressed by the Austrian economist J.A. Schumpeter Dr. Kalam's social thoughts are soiled with deep native roots as his economic thoughts are manifested from salient indigenous branches. Dr. Kalam's socio economic ideas India 2020 vision Developed India Knowledge driven Societal Transformation PURA Quality Electricity for all Public Private Partnership Perspectives Creative Leadership New Work Culture Elimination of Corruption and Social Amity are interpreted in simple language with illustrations and model intelligible to all readers. A world list of Dr. Kalam's pet words and phrases and their related themes is added for the better understanding of Kalamism.
Keywords: "Kalam,A.P.J. Abdul"